Physical Exercise Improves Cognitive Function Together with Microglia Phenotype Modulation and Remyelination in Chronic Cerebral Hypoperfusion - Jiang, Ting; Zhang, Liying; Pan, Xiaona; Zheng, Haiqing; Chen, Xi; Li, Lili; Luo, Jing; Hu, Xiquan (Frontiers in Cellular Neuroscience, 2017)
Myelin is closely associated with cognitive function and is extremely vulnerable to damage in ischemic cerebrovascular diseases. The failure of remyelination is mainly due to limitations in oligodendrocyte progenitor cells (OPCs) differentiation in the damaged area. Previous studies have shown that physical exercise can improve vascular cognitive impairment, but whether it can reverse the defect in remyelination during ischemic injury and the underlying mechanism remains unclear. In this study, we observed the effects of physical exercise on chronic cerebral hypoperfusion (CCH) established by bilateral carotid artery occlusion. The cognitive function, myelin integrity , OPCs proliferation and differentiation, as well as microglia polarization were analyzed at 28 days after CCH. Besides, the expression of CX3CL1/CX3CR1 axis and activation of mitogen-activated protein kinase (MAPK) signal cascades were also evaluated. We found that physical exercise improved the cognitive function of rats with CCH, alleviated myelin injury, triggered OPCs proliferation and differentiation, facilitated microglia polarization toward M2, augmented the expression of CX3CL1/CX3CR1 axis, and reduced ERK and JNK phosphorylation. The results indicated that physical exercise improved the cognitive function of rats with CCH, possibly through microglial phenotype modulation and enhancement of oligodendrocytegenesis and remyelination. Moreover, the CX3CL1/CX3CR1 axis plays an important role in this process by mediating ERK- and JNK-dependent pathways.